KONSEP URANG SABANA URANG DALAM PEPATAH ADAT MINANGKABAU - Mustansyir, Rizal; Munir, Misnal (Jurnal Filsafat "WISDOM", 2009)
AbstractAccording to Wilhelm Diltheyâs hermeneutic perspective,there are six points in reinterpreting the Minangkabauâs traditional aphorism âUrang sabana urangâ. First, understanding of Minangkabauâs way of life is a general process, included in an ordinary life which is expressed in the aphorism. Second, theexpression of the aphorism is called âausdruckâ, Minangkabauâsexpression of life experiment and historicity. Third, humancharacteristics in Minangkabauâs aphorism consist of: âurang,urang-urang, tampan urang, angkuh-angkuh urang, urangurangan, urang sabana urangâ. Fourth, âurang sabana urangâ is a man who has excellent characteristics. Fifth, the globalization influence and the modern culture have changed Minangkabauâs insight of âurang sabana urangâ concept so that it needs a reinterpretation in order to be understood by youth of Minang. Sixth, the epistemological dimension in Minangkabauâs aphorism synthesizes an empirical aspect and rationality. The metaphysical dimension of the aphorism shows a relation between tradition and religion so that it arise the principle of âadat basandi syarak, syarak basandi kitabullahâ. The axiological dimension in the aphorism is seen as a criterion of values which is an obligation for Minangs to prevent their identity asâ urang sabana urangâ.Keyword: urang sabana urang, adat basandi syarak, syarakbasandi kitabullah, Minangkabau custom aphorism.